2019
DOI: 10.23917/varidika.v30i2.7571
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Problems on Teaching English for Young Learners at Al – Azhar 55 Islamic Primary School Yogyakarta and How to Solve Them

Abstract: The present paper aims to reveal the problems faced by teachers when teaching English for second – grade students at Al – Azhar 55 Islamic Primary Schoolin Yogyakarta. This bilingual school is considered as a pilot project which began theprogram in July 2016. There are only 2 classes which are the first and second grade.However, this study involved 21 second-grade students, 2 homeroom teachers, and 1native speaker. Qualitative method was applied in this study by combining documentanalysis, observation, and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 5 publications
2
15
0
1
Order By: Relevance
“…When they are at home, they only use their mother tongue. It is in line with Widodo and Dewi (2018), mentioning that English is not a tool of communication for them. It arises a problem for teachers because they have to try harder to make the students use English.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…When they are at home, they only use their mother tongue. It is in line with Widodo and Dewi (2018), mentioning that English is not a tool of communication for them. It arises a problem for teachers because they have to try harder to make the students use English.…”
Section: Discussionsupporting
confidence: 77%
“…Another problem faced by English teachers is noisy students because they disturb their friends, as said by Nurasiah (2017) and Widodo and Dewi (2018). When they are noisy, their friends cannot concentrate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the novice teachers will explain carefully since the students are lower primary students who need extra treatment. The same opinion comes from [29], providing preparation class at the beginning of semester for the students who struggle in using English or Bahasa Indonesia to communicate will help the students a lot.…”
Section: Novice English Teachers' Challenges In Bilingual School and The Solutionsmentioning
confidence: 93%
“…There are several previous studies related to the problems and challenges encountered by the teachers in bilingual schools conducted by [9], [2], [8], [25], [29], [24], and [6]. From those studies, it is concluded that there are several problems and challenges faced by the teachers in bilingual schools.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation